How to innovate continuously? Conceptualizing generative capability - Jinyu Guo; Lin Cui; Li Sun; Bo Zou (Journal of Innovation & Knowledge (JIK), 2022)
This study conceptualizes the novel concept of generative capability, a unique capability by which firms organize experiential learning activities to achieve fast and iterative innovation. Employing a mixed-method research design, we first explored the theoretical framework of generative capabilities through an inductive case study to identify its dimensions. On this basis, we also developed measurement scales for generative capability. We then used survey data on a sample of 212 Chinese firms to test the construct and criterion validity of generative capability. Our findings show that generative capability can be captured by a second-order reflective construct with the three dimensions of knowledge acquisition, knowledge inheritance, and knowledge updating, and that capability is positively associated with firm innovation performance.
Keywords: 650; Continuous product innovation; Generative capability; Mixed-method; Sustained product innovation